Foundational Gender Theory for a Dangerous World: Intersectional Gender Seminar in the Fight against Rape Culture - Flavia Vidal; Tasha Hawthorne (Social Sciences, 2017)
This paper focuses on a team-taught gender studies colloquium in the spring term of 2016 at Phillips Academy at Andover. Having heard the loud and clear message coming down from college campuses and being familiar with their harrowing statistics of gender-based violence and sexual assault, we knew that we must educate high-school students about gender theory, gender-based violence, and sexual-assault prevention as early as possible. The course introduced students to foundational texts in intersectional gender theory and key concepts as they are understood and used in critical interdisciplinary studies of gender. We explored how these concepts are taken up from different perspectives to address specific social problems, particularly rape culture—actions, events, and attitudes that normalize, trivialize, and highlight an overarching pattern of sexual assault, more often than not directed at women—and the implications of these critical approaches for thinking about and acting in the world.